Effect of Different Types of High-Fat Diet (HFD) for Induction of Type 2 Diabetes Mellitus in Animal Model - Dewistamara, Marshellia Ghinanda; Qomariyah, Nur; Khaleyla, Firas (LenteraBio : Berkala Ilmiah Biologi, 2025)
Consumption of fast food increase the risk of type 2 diabetes mellitus (T2DM) through excessive fat accumulation in adipose tissue, insulin resistance, and β-cell dysfuntion. Studies comparing different fat types for T2DM induction are scarce. This study aims to identify the optimal fat type for T2DM induction in animal model, based on cholesterol increase rate and blood glucose stability. The induction of T2DM was performed using high-fat diet (HFD) for 8 weeks and alloxan intraperitoneally. The HFD consist of 80% standard feed, 15% fat sources (palm oil, beef tallow, or goat tallow), and 5% duck egg yolk. This study used a completely randomized design with 20 male DDY mice grouped into five treatment groups. T2DM was assessed based on fasting blood glucose levels and islet diameter of Langerhans in mice. Data of fasting blood glucose levels were analyzed using ANOVA and Duncan's test. Data on islet diameter were analyzed using Kruskal-Wallis and Dunnett's test. The results showed that different fat types had a significant effect (p<0.05) in induced T2DM. Among the three types of fat, beef tallow was the most optimal for inducing T2DM according to its ability to increase cholesterol levels and stability in maintaining blood glucose levels.